Sonographic spectrum of first‐trimester fetal cephalocele: review of 35 cases. (4th June 2015) - Sepulveda, W.; Wong, A. E.; Andreeva, E.; Odegova, N.; Martinez‐Ten, P.; Meagher, S.
ABSTRACT Objective To describe the sonographic features of fetal cephalocele diagnosed at the time of first‐trimester ultrasound screening for aneuploidy. Methods This was a retrospective review of cases of cephalocele diagnosed in the first trimester at four fetal medicine referral centers. Once diagnosis was suspected, a transvaginal ultrasound examination was offered to improve depiction of the cranial defect and enhance examination of fetal anatomy, with special attention given to the location, size and content of defects. To assure consistency in diagnosis, representative pictures and videoclip sequences of the cranial defect were obtained and reviewed by at least two authors. Cases were classified and compared with the assessment made at diagnosis. Results Of the 35 affected fetuses identified, 33 were of a singleton pregnancy and two were of twin pregnancies in which the other fetus was unaffected. The lesion was classified as a cranial meningocele in 13 (37%) cases and as an encephalocele in 22 (63%). The bone defect was occipital in 27 (77%), frontal in three (9%), parietal in three (9%) and non‐classifiable in two (6%). Twelve (34%) were considered as small in size, 11 (31%) as medium and 12 (34%) as large. There were no reported cases of aneuploidy; however, four (11%) cases were associated with Meckel–Gruber syndrome, two (6%) with a disruptive syndrome and one (3%) with skeletal dysplasia. Eight (23%) pregnancies were lost to follow‐up. Parents opted for termination of pregnancy in 21 of the 27 remaining cases and, of the six ongoing pregnancies, four patients miscarried or the fetus died in utero during the second trimester, one liveborn infant died shortly after delivery and one underwent neonatal surgery for an isolated cranial meningocele and is currently doing well. Conclusions First‐trimester sonographic diagnosis of cephalocele is accomplished easily with a detailed examination of the skull contour at the time of routine assessment of the axial and sagittal views of the head for measurement of the biparietal diameter and nuchal translucency, respectively. However, the sonographic features are highly variable. A significant proportion of cases are associated with genetic or disruptive syndromes. Prenatal diagnosis of cephalocele in the first trimester was associated with a high rate of termination of pregnancy and early intrauterine fetal demise. Only one fetus in this series survived and is neurologically intact; therefore, the prognosis of this condition remains poor. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.